PARADOKS DIGITALISASI TATA KELOLA MADRASAH SWASTA: KETEGANGAN ANTARA STANDARDISASI NASIONAL DAN OTONOMI PENDIDIKAN ISLAM - Randa; Akhmad Muaddin; Muchammad Eka Mahmud (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the construction of national digital bureaucratic management standardization regulations in private madrasahs, identify the conce ptual tensions between national digital regulations and the fundamental values of Islamic Educational Management, and reconstruct an ideal governance model for private madrasahs in the era of macro digitalization. This research employed a qualitative approach using a library research method. Primary data consisted of national regulatory documents such as e-Kinerja, Platform Merdeka Mengajar (PMM), e-RKAM, and the automated accreditation system, while secondary data were obtained from books, scientific journals, and relevant previous studies. Data analysis techniques used qualitative content analysis and critical discourse analysis. The findings reveal that national digital regulations are constructed upon the paradigm of Digital Era Governance (DEG), which generates bureaucratic standardization and depersonalization within private madrasah governance. These policies impose significant digital administrative burdens and contribute to the erosion of khidmah, istighna’, and barakah values within the organizational culture of Islamic education. As a solution, this study proposes the Hybrid Autonomy Management model, a governance framework that integrates digital administrative compliance with the protection of spiritual autonomy and institutional independence in private Islamic educational institutions. This model is implemented through governance zone differentiation, delegation of digital administrative tasks to specialized operators, and strengthening waqf-based financial sustainability.